2022
DOI: 10.1111/dar.13438
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards dependent drinking and its role on caregiving burden: A qualitative study from Goa, India

Abstract: Introduction. Stigma towards alcohol use disorders is prevalent in India and can lead to social exclusion and hamper treatment access and outcomes. Family members of individuals with dependent drinking are often their primary caregivers and play a key role in decisions around help-seeking, treatment and recovery. The nature and role of stigma in caregiving, and the consequent burden on family caregivers of those with dependent drinking, has not been qualitatively studied in India. Methods. We conducted in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…Thus, incorporating this group into the account would help better understand the burden of alcohol posed to the liver (65,66). Third, the societal bias and more significant disapproval directed toward alcohol use in women, compared with men, is a significant factor (67). This societal influence might result in the underreporting of alcohol consumption in women, making it difficult to discern trends and patterns accurately.…”
Section: Livermentioning
confidence: 99%
“…Thus, incorporating this group into the account would help better understand the burden of alcohol posed to the liver (65,66). Third, the societal bias and more significant disapproval directed toward alcohol use in women, compared with men, is a significant factor (67). This societal influence might result in the underreporting of alcohol consumption in women, making it difficult to discern trends and patterns accurately.…”
Section: Livermentioning
confidence: 99%
“…The economically more prosperous states (e.g., Goa and Kerala) are expected to exhibit higher rates of diabetes compared with the other states (e.g., Rajasthan), which is specically mediated by higher caloric diets and much lower levels of physical exercise. [24][25][26] Preliminary observations from a survey reported by the Indian Council of Medical Research (ICMR) revealed that Jharkhand and Chandigarh have 0.96 and 0.12 million DM cases, compared to that of Maharashtra and Tamilnadu, showing 9.2 and 4.9 million, respectively. The national survey reported in various metropolitan cities suggests similar trends, i.e., 11.8% in Kolkata, 11.6% in New Delhi, 9.3% in West India and 6.1% in Kashmir Valley compared to Hyderabad, Chennai and Bangalore, which showed 16.6%, 13.5% and 12.4%, respectively.…”
Section: The Status and Prevalence Of Diabetes Mellitus (Dm) And Diab...mentioning
confidence: 99%
“…, Rajasthan), which is specifically mediated by higher calorific diets and much lower levels of physical exercise. 24–26 Preliminary observations from a survey reported by the Indian Council of Medical Research (ICMR) revealed that Jharkhand and Chandigarh have 0.96 and 0.12 million DM cases, compared to that of Maharashtra and Tamilnadu, showing 9.2 and 4.9 million, respectively. The national survey reported in various metropolitan cities suggests similar trends, i.e.…”
Section: The Status and Prevalence Of Diabetes Mellitus (Dm) And Diab...mentioning
confidence: 99%
“…Families are adversely affected by AUDs, and they also play a critical role in the development of, as well as recovery from, AUDs (Copello et al, 2005 ). Additionally, in LMICs, traditional family structures, prevailing stigma around AUDs, and cultural beliefs held by family members can influence help-seeking, and also negatively influence recovery processes (Kumar et al, 2022 ).…”
Section: Innovations To Improve Access To Care For Auds In Lmicsmentioning
confidence: 99%